Impact of Dysphagia Severity on Clinical Decision Making via Telerehabilitation - Ward, Elizabeth C. (Mary Ann Liebert, Inc., 2014)
Objective: Recent research supports the proposal that valid and reliable clinical swallow examinations (CSEs) can be conducted via telerehabilitation. However, no studies have explored whether dysphagia severity has an impact on the success of the session or its outcomes. The current study examined how dysphagia severity impacted on either (a) clinical decision making for safety of oral intake or (b) clinician perceptions of CSEs conducted via telerehabilitation. Subjects and Methods: One hundred patients (25 nondysphagics and 25 mild, 25 moderate, and 25 severe dysphagics) were assessed using a telehealth system and methodology reported in prior research. For each assessment, the online and face-to-face (FTF) clinicians simultaneously completed a structured CSE. On session completion, the online clinician indicated level of agreement with two statements regarding the level of rapport and ability to competently assess the patient. Results: In each of the four groups, acceptable levels of agreement were observed between raters for the three primary outcomes (decisions regarding oral/nonoral intake and safe food and fluids) as well as over 90% of the CSE items. Clinicians agreed they could develop good rapport with the majority of patients in all groups. However, for a small but significant (p<0.5) proportion of patents in the severe dysphagic group, clinicians disagreed they were able to satisfactorily and competently assess to the best of their abilities using the telerehabilitation system. Conclusions: Clinical decisions made during and as an outcome of the total CSE were found to be comparable to those made in the FTF environment regardless of dysphagia severity. Clinicians noted some difficulty assessing patients with greater complexity, which occurred in greater numbers in the group with severe dysphagia.